Cell softness regulates tumorigenicity and stemness of cancer cells. (4th December 2020) - Lv, Jiadi; Liu, Yaoping; Cheng, Feiran; Li, Jiping; Zhou, Yabo; Zhang, Tianzhen; Zhou, Nannan; Li, Cong; Wang, Zhenfeng; Ma, Longfei; Liu, Mengyu; Zhu, Qiang; et al.
Abstract: Identifying and sorting highly tumorigenic and metastatic tumor cells from a heterogeneous cell population is a daunting challenge. Here, we show that microfluidic devices can be used to sort marker‐based heterogeneous cancer stem cells (CSC) into mechanically stiff and soft subpopulations. The isolated soft tumor cells (< 400 Pa) but not the stiff ones (> 700 Pa) can form a tumor in immunocompetent mice with 100 cells per inoculation. Notably, only the soft, but not the stiff cells, isolated from CD133 +, ALDH +, or side population CSCs, are able to form a tumor with only 100 cells in NOD‐SCID or immunocompetent mice. The Wnt signaling protein BCL9L is upregulated in soft tumor cells and regulates their stemness and tumorigenicity. Clinically, BCL9L expression is correlated with a worse prognosis. Our findings suggest that the intrinsic softness is a unique marker of highly tumorigenic and metastatic tumor cells. Synopsis: Cellular stiffness has been associated with stem cell‐like properties in development and cancer. Here, mechanical softness associated with high expression of the transcriptional regulator BCL9L is identified as a general marker of cancer stem cells. Microfluidic sorting allows tumor cell separation according to their mechanical stiffness. Soft tumor cells show increased tumorigenicity in vivo . BCL9L is a regulator of stemness in soft tumor cells. BCL9L levels and tumor cell softness correlate with disease progression in melanoma, breast and colon cancer patients. Abstract : Intrinsic mechanical properties and BCL9L expression in tumor cells determine their stemness and are linked to cancer progression.